STUDI KASUS PADA LANSIA DIABETES MELITUS DENGAN KETIDAKSTABILAN GULA DARAH - Isna Aglusi Badri; Cindya Lorenza; Inke Asmika (Ensiklopedia of Journal, 2023)
Elderly is someone who has reached the age of 60 years and over, the final period of life in which a person experiences a progressive decline in physical, cognitive, and so on which results in an increase in the burden on the health system. Diabetes mellitus is a progressive chronic disease characterized by the body's inability to metabolize carbohydrates, fats and proteins leading to hyperglycemia. The general purpose of this study was to describe gerontic nursing care for Tn.S and Mrs.Z in Diabetes mellitus with the main problem being instability of blood sugar levels related to the inability of the family to care for the elderly, and to give boiled red betel leaf as a lowering of high blood sugar levels. The method used is a descriptive method (case study) by collecting data using a gerontic nursing care format, namely interviews, observations and physical examinations. The results of the research from the nursing actions carried out during the five-day visit were that both the patient's family and the patient were able to recognize health problems, were able to decide on appropriate actions to treat family members, were able to care for family members who experienced unstable blood sugar levels, were able to use health facilities. Based on the results of the gerontic nursing care carried out, it is hoped that it can be used as learning material and reference material in providing nursing care to Diabetes Mellitus patients.